Agriculture, Health, and Nutrition: Toward Conceptualizing the Linkages - Hoddinott, John F. (International Food Policy Research Institute, 2012)
Agriculture and health and nutrition have long occupied separate realms. Analyses of agricultural production seldom recognize that health status affects productivity, nor do they recognize that agricultural goods and processes have health consequences. At the policy and programmatic levels, agriculture and health operate in separate silos, seldom considering the consequences of their actions on sectors outside their own. This separation is strange given that agriculture and health and nutrition are tightly wedded. Agriculture is the primary source of calories and essential nutrients and is a major source of income for the world’s poor, while agriculture-related health losses are massive.